ANALISIS KURIKULUM PENDIDIKAN DI TAMAN KANAK KANAK ANGGREK KECAMATAN SUKARAMI PALEMBANG - Puspita Sari, Agnes; Irtika, Rindi; Dwi Anugrah, Dessy; Cahya Puspita, Marisa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This research was motivated by the uniqueness of the K13 curriculum which attracted researchers to carry out research to analyze the curriculum in Orchid Kindergarten. The aim of this research was to analyze the educational curriculum in relation to the vision, mission and objectives. Data collection techniques are carried out by examining the results of observations, interviews and documentation with the research object. Analysis was carried out using data triangulation techniques. As a result of the research, the curriculum aims to develop faith and devotion to Allah SWT, grow and increase children's awareness of practicing Islamic teachings. The curriculum material develops 6 aspects of development, namely moral and moral values, physical and motoric, cognitive, language, social, emotional, artistic. In implementing learning, teachers use various methods, specifically for instilling moral and religious values, implemented through habituation activities carried out every day. Educational evaluation techniques use performance, assignments, and observation